From simulation to reality : assessing the efficacy of pure pursuit, MPC, and MPCC on the F1Tenth platform - Kong, Xiangyiming (Stellenbosch : Stellenbosch University, 2025)
Kong, X. 2025. From Simulation to Reality: Assessing the Efficacy of Pure Pursuit, MPC, and MPCC on the F1Tenth Platform. Unpublished masters thesis. Stellenbosch: Stellenbosch University [online]. Available: https://scholar.sun.ac.za/items/a9c1084b-d0fa-47a3-9229-928d6153fac7